Synthesis and Characterization of 4-Amino-quinazoline Derivatives - Yan, He-Ping; Zhou, Bo; Gou, Gao-Zhang; Zhang, Ju-Cheng; Xu, Shi-Juan; Liu, Wei (Asian Journal of Chemistry, 2015)
Four 4-amino-quinazoline compounds, including 7-[3-(2-methoxyphenoxy)propoxy]-N'-(3-chlorophenyl)-6-methoxyquinazolin-4-amine, 7-[3-(4-methoxyphenoxy)propoxy]-N'-(3-chlorophenyl)-6-methoxyquinazolin-4-amine, 2-[3-4-(3-chlorophenylamino)-6-methoxy-quinazolin-7-yloxypropoxy]benzaldehyde, 4-[3-4-(3-chlorophenylamino)-6-methoxyquinazolin-7-yloxypropoxy]benzaldehyde, were synthesized from N'-[5-(3-chloropropoxy)-2-cyano-4-methoxyphen-yl]-N,N-dimethylformamidine by cyclization and etheration. The yields of the compounds IIIa-d were 70.3, 71.0, 45.5 and 50.2 %, respectively. Their structures were characterized by IR, 1H NMR, 13C NMR, MS and elemental analysis.